Visible light‐driven acridone catalysis for atom transfer radical polymerization. Issue 10 (4th February 2022) - Wei, Donglei; Li, Huili; Yang, Chuanqing; Fu, Jianmin; Chen, Hou; Bai, Liangjiu; Wang, Wenxiang; Yang, Huawei; Yang, Lixia; Liang, Ying
Abstract: Acridone as a new kind of visible light photocatalyst has been developed to catalyze metal free atom transfer radical polymerization (ATRP). The photocatalyst possess low excited state potential as can undergo an oxidative quenching pathway to initiate ATRP of vinyl monomers. Kinetic study and light on/off reaction demonstrate the "living"/controlled nature of the polymerization by light. Block copolymers can be achieved by using PMMA as macroinitiator to reinitiate polymerization of other vinyl monomers, which shows highly preserved Br chain‐end functionality in the synthesized polymers. Moreover, the polymerization can be conducted under air atmosphere as most photocatalysts need anaerobic condition, which may give inspiration of further application of this kind of photocatalyst. Abstract :